Integrative multi-omics and experimental analyses implicate PTK2 as a lorazepam-associated biomarker and potential therapeutic target in ovarian cancer - Hong, Xia; He, Xingjun; He, Suli (Frontiers in Pharmacology, 2026)
BackgroundOvarian cancer remains one of the most lethal gynecologic malignancies, characterized by high recurrence rates and chemoresistance. Recent advances suggest that neuroactive drugs such as lorazepam may exert off-target molecular effects beyond the central nervous system. However, their pharmacological relevance in tumor biology remains largely unexplored. This study aimed to identify and validate shared molecular targets of lorazepam and ovarian cancer, uncovering novel biomarkers and therapeutic mechanisms.MethodsPotential lorazepam targets were retrieved from the CTD, STITCH, and SwissTargetPrediction databases and cross-referenced with ovarian cancer–related genes from GeneCards. Bioinformatic analyses were conducted, including target screening, protein–protein interaction network construction, Lasso–Cox modeling, and functional enrichment. We further performed immune infiltration profiling, single-cell and spatial transcriptomics analyses, followed by experimental validation using qPCR, CCK-8, colony formation, wound-healing, and flow cytometry assays.ResultsFifty-one overlapping genes were identified between lorazepam and ovarian cancer, with PTK2 emerging as a central hub gene. PTK2 overexpression was significantly associated with poor prognosis, enhanced immune activation, stromal remodeling, and metabolic reprogramming. Spatial transcriptomics revealed PTK2 enrichment in malignant and fibroblast-rich regions. Functional assays confirmed that stable PTK2 knockdown inhibited proliferation, colony formation, and migration while promoting apoptosis in ovarian cancer cells.ConclusionOur findings suggest that PTK2 may act as a putative oncogenic mediator and potential pharmacological link between lorazepam signaling and ovarian cancer progression. PTK2 functions as a biomarker and druggable target that integrates tumor growth, immune modulation, and metabolic adaptation. Targeting PTK2 may provide a promising therapeutic strategy for precision oncology and rational drug repurposing.